PEMBENTUKAN KARAKTER SEMANGAT KEBANGSAAN DAN CINTA TANAH AIR PADA SISWA MELALUI SANGGAR SENI MUSIK TEKU-TEKU DI SMP NEGERI 15 PALU - Pratama, Rezan Agung; Juraid, Juraid; Amus, Sunarto (Katalogis, 2020)
This study aims to find out and analyze (1) aspects of national character and nationalist spirit formation in a teapot music art studio in Palu 15 Junior High School, and (2) efforts made by the tumbling music art studio SMPN 15 Palu in shaping character the spirit of nationalism and love for the country. This type of research is a descriptive study with a qualitative approach obtained from observations, interviews and in-depth interviews with the results of the study illustrating that there are several aspects of character building in the spirit of nationalism and love for the country which have been carried out at the Palu Palu State Middle School introduction, application, repetition / habituation and internalization into character. The efforts that have been made are to familiarize students in collaborating with peer groups despite different ethnicity, ethnicity, and social status in resolving a problem, involving students in organizing the commemoration of national heroes' day through a teapot music art studio SMPN 15 Palu, conducting a visiting program place of history or learn about the history of traditional music in the city of Palu, involving students in celebrations on national holidays, habituation to the use of domestically-made products (traditional musical instruments), habituation of the use of good and correct Indonesian language when joined in a troupe of music art music in SMPN 15 Palu, providing information from printing sources and electronics about the richness of Indonesian nature and culture